Branding Models - Zhelev, Simeon (Research Papers, 2010)
The understanding that branding (the process of building a brand) should be the main organizing principle of modern business is seldom challenged (at least apparently) in the academic literature. In the business field it also receives strong support. Then, why in the regular business practice there are more cases of chaotic branding, spontaneous and uncoordinated branding initiatives, branding processes without conceptual platform to support them, etc.?The present work adheres to the understanding that the main reason for this situation is the lack of systematization and taxonomy of the branding models. Under branding models I understand (1) the manner in which brand is perceived as a social, economic, cultural, psychological, semiotic phenomenon, (2) all standpoints for its creation and (3) indications and means for recognizing whether the brand is successfully created. Therefore, every brand model should meet the prerequisite to answer three questions as a matter of principle such as:What is brand?How do you build a brand?How to recognize success in creating a certain brand?The first question refers to theessence of the brand; the second one to the activities for building a brand; and the third – theindications that will identify whether and how successful the created brand is. Besides the instrumental function (what to do), the models have axiological (evaluation) function as well - whether the measures taken correspond to the initially expected.The paper presents and critically discusses five branding models: cognitive, emotional, viral, cultural and model of salience, each of which has its standpoints in response to the above three basic questions.